(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the role of the endocrine system in the development, physiological activity and health of the mammary gland based on scientific sources. The anatomical and functional state of the mammary gland is closely related to the activity of the hypothalamic-pituitary-ovarian axis, thyroid gland, adrenal glands and metabolic hormones. The effect of estrogen, progesterone, prolactin, oxytocin, thyroid hormones, insulin and other biologically active substances on the development and function of the mammary gland is analyzed.